Factors contributing to nursing team work in an acute care tertiary hospital. Issue 1 (February 2017) - Polis, Suzanne; Higgs, Megan; Manning, Vicki; Netto, Gayle; Fernandez, Ritin
Summary: Background: Effective nursing teamwork is an essential component of quality health care and patient safety. Understanding which factors foster team work ensures teamwork qualities are cultivated and sustained. Objective: This study aims to investigate which factors are associated with team work in an Australian acute care tertiary hospital across all inpatient and outpatient settings. Methods: All nurses and midwives rostered to inpatient and outpatient wards in an acute care 600 bed hospital in Sydney Australia were invited to participate in a cross sectional survey between September to October 2013. Data were collected, collated, checked and analysed using Statistical Package for the Social Sciences (SPSS) Version 21. Factors reporting a significant correlation with where p  < 0.05 were analysed in a multiple regression model. Results: A total of 501 surveys were returned. Nursing teamwork scores ranged between 3.32 and 4.08. Teamwork subscale Shared Mental Model consistently rated the highest. Mean scores for overall communication between nurses and team leadership were 3.6 (S.D. 0.57) and 3.8 (SD 0.6) respectively. Leadership and communication between nurses were significant predictors of team work p  < 0.001. Conclusion: Our findings describe factors predictive of teamwork in an acute care tertiary based hospital setting across inpatient and outpatient specialty units. Our findings are of particular relevance in identifying areas of nurse education and workforce planning to improve nursing team work.